From community to consumption new and classical themes in rural sociological research - Bonanno, Alessandro (Research in rural sociology and development ;, 2010)
This edited book contains salient papers presented at the XII World Congress of Rural Sociology held in South Korea in 2008. These papers have been selected for their quality and have undergone a peer review process. The rationale behind this book rests on the desire to share the wealth of research presented at the World Congress with interested individuals who could not attend the event and it reflects the empirical work and thinking characterizing contemporary rural sociology. As this sociological sub-discipline evolves along with society and the rural world, it appears of paramount importance to make available ground-breaking research to the international scientific community. Rural sociology is changing and this volume testifies of this change by documenting the introduction of new themes of research as well as the evolution of established ones. In this regard, it provides a unique and uniquely international view of the most recent advanced production in rural sociology. The volume consists of eighteen chapters representing original pieces of research and an introduction that frames them in the context of the evolution of the discipline.